StAP1 phage: an effective tool for treating methicillin-resistant Staphylococcus aureus infections - Lu, Yuwen; Lu, Yifei; Li, Baobao; Liu, Jiazhen; Wang, Lixin; Zhang, Lianyang; Li, Yang; Zhong, Qiu (Frontiers in Microbiology, 2023)
Introduction Staphylococcus aureus infection has long been a serious concern in the medical field, with methicillin-resistant Staphylococcus aureus (MRSA) posing a considerable challenge to public health. Given the escalating bacterial resistance and the favorable biosafety and environmental properties of phages, the resurgence of phage therapy offers a promising alternative to antibiotics. Methods In this study, we isolated and characterized a MRSA phage named StAP1 from a Chinese hospital. Phenotypic and molecular analyses revealed its broad-spectrum characteristics, genomic background, and potential application in MRSA infection treatment. Results Morphological examination classified the phage as a member of the Herelleviridae phage family, displaying a typical hexagonal head and a slender fibrous tail. Genomic analysis unveiled a size of ~144,705 bp for the StAP1 genome, encompassing 215 open reading frames (ORFs). The one-step growth curve demonstrated a 20-min incubation period for the phage, with an optimal multiplicity of infection (MOI) of 0.1. Moreover, StAP1 exhibited stability across a wide range of temperatures and pH levels. Further investigation of its broad-spectrum characteristics confirmed its ability to effectively infect all staphylococcal cassette chromosomal mec (SCCmec) types found in MRSA strains, notably displaying a remarkable lysis rate of 76.7% against the prevalent ST239 strain in China. In vivo studies show cased significant efficacy of the StAP1 phage against MRSA infection. Discussion Overall, StAP1 phage presents a broad infection spectrum and exhibits strong lytic effects on various MRSA strains, highlighting its tremendous potential as a powerful tool for MRSA infection treatment.